Cuisenaire Beam Media on Increasing Cognitive Ability of Preschool Age Children in Raudathul Atfhal Kindergarten Al-insyiroh, kendari city - Armayani; Faridah Moh Said (Fakultas Kesehatan IKesT Muhammadiyah Palembang, 2023)
One form of measurement of early childhood growth and development (fine and gross motor coordination), intelligence (thinking power, creativity, emotional intelligence, spiritual intelligence), and socio-emotional children. Cognitive ability is one aspect of development related to the ability to think cognitively on activities or processes of acquiring knowledge. The method of playing in learning in Kindergarten is a technique of delivering information aimed at children through game tools. Media Cuisenaire blocks are blocks of ten levels from one to ten which are equipped with numbers one to ten and are equipped with different colors as a means of improving aspects of development related to thinking skills in children. This type of research is quantitative with the form of design used is pre- experimental with a one-group pre-test post-test design. The population in this study were 85 students of preschool age at Raudathul Atfhal Al-Insyiroh Kindergarten, Kendari City, with a sampling technique using simple random sampling with a sample of 40 respondents. The test used is the Paired Sample t. The results showed that there were differences in the improvement of children's abilities before and after the Play Beam Cuisenaire media was carried out. In this study, the results of the paired sample- Test test obtained that the p value (0.000) > (0.05), and the t value (7.550). The conclusion is that there is an effect of Play Beam Cuisenaire media on improving the cognitive abilities of preschoolers in Raudathul Atfhal Al-Insyiroh Kindergarten, Kendari City.